Re-do robot-assisted salvage lobectomy after esophagectomy with gastric pull-up reconstruction: a case report - Ghada Shahin; Rohit Kharbanda; Quirijn Tummers; Jerry Braun (World Journal of Surgical Oncology)
Abstract Background Robot-assisted Thoracic Surgery (RATS) is well-established for complex minimally invasive thoracic surgery. Despite the available literature, robotics for complex advanced NSCLC for re-do surgery remains underexplored. Case presentation We present a 55-year-old female who underwent esophagectomy with gastric pull-up reconstruction for squamous cell carcinoma (SCC) of the esophagus (cT3N2M0, stage IIIB) after neo-adjuvant concurrent chemoradiation therapy (ypT2N1 stage IIB disease). Six years later, computed tomography (CT) scan showed stage IA Thyroid Transcription Factor-1 (TTF-1) positive adenocarcinoma in the left upper lobe treated by stereotactic radiotherapy. Two years later, a SCC of the right upper lobe (RUL) was found (Fig. 1). Although locoregional therapy was preferred Pembrolizumab® was initiated with curative intent as the tumor demonstrated a high Programmed Death-Ligand 1 (PD-L1) expression. Follow-up CT-scan showed no biological response. Salvage lobectomy was proposed, and patient consent obtained. As demonstrated in the video, RATS provided great exposure to the adhesions, vascularization of the neo-oesophagus and maximal dexterity in difficult spaces. Conclusions This case demonstrates the value of RATS in complex re-do thoracic surgery after immunotherapy and previous thoracotomy. Graphical Abstract Robot-Assisted Thoracic Surgery in Re-do Lung Surgery